Neuroendocrine mechanisms underlying estrogen positive feedback and the LH surge - Kauffman, Alexander S. (Frontiers in Neuroscience, 2022)
A fundamental principle in reproductive neuroendocrinology is sex steroid feedback: steroid hormones secreted by the gonads circulate back to the brain to regulate the neural circuits governing the reproductive neuroendocrine axis. These regulatory feedback loops ultimately act to modulate GnRH secretion, thereby affecting gonadotropin secretion from the anterior pituitary. In females, rising estradiol (E2) during the middle of the menstrual (or estrous) cycle paradoxically “switch” from being inhibitory on GnRH secretion (‘negative feedback’) to stimulating GnRH release (‘positive feedback’), resulting in a surge in GnRH secretion and a downstream LH surge that triggers ovulation. While upstream neural afferents of GnRH neurons, including kisspeptin neurons in the rostral hypothalamus, are proposed as critical loci of E2 feedback action, the underlying mechanisms governing the shift between E2 negative and positive feedback are still poorly understood. Indeed, the precise cell targets, neural signaling factors and receptors, hormonal pathways, and molecular mechanisms by which ovarian-derived E2 indirectly stimulates GnRH surge secretion remain incompletely known. In many species, there is also a circadian component to the LH surge, restricting its occurrence to specific times of day, but how the circadian clock interacts with endocrine signals to ultimately time LH surge generation also remains a major gap in knowledge. Here, we focus on classic and recent data from rodent models and discuss the consensus knowledge of the neural players, including kisspeptin, the SCN, and glia, as well as endocrine players, including estradiol and progesterone, in the complex regulation and generation of E2-induced LH surges in females.